Dialogue in Dialog: Stem Cells (Dialog, 2002)
Karen Lebacqz, Stem Cells and Justice, p.231 Margaret Mclean, Stem Cells: Justice at the Gate, p.236 Paul Lauritzen, Expanding the Debate Over Stem Cell Research, p.238 Karen Lebacqz, Response to Lauritzen and McLean, p.240 Ted Peters and Gaymon Bennett, Cloning in the White House, p.241